Development of a Form to Assess the Self-Care Competence of the Person with a Tracheostomy - Queirós, Sílvia (2015)
Background: The development of the self-care competence in the person with a tracheostomy is described as a key driver for a healthy transition to life with a tracheostomy. An instrument for assessing the self-care competence of the person with a tracheostomy contributes to nurses’ decision-making and promotes the quality of care. Objectives: To develop a tool for assessing the self-care competence of the person with a tracheostomy. Methodology: A methodological study was conducted. Content validity was obtained through the judgment of experts, with a focus group methodology. Reliability was assessed using Cronbach’s alpha coefficient. The instrument was applied to a sample of 80 participants, using a non-probability convenience sampling technique. Results: The study resulted in a form with 39 indicators, divided into 6 areas, which showed good internal consistency (alpha = 0.89) and recognised content validity. Conclusion: The final version of the form is applicable, and has the potential to be used in future studies on its validity.